Integration of nurse-led virtual reviews with growth hormone device-linked patient adherence information: a mixed methods feasibility study - Helen Stokes; Julie Jones; Chris Worth; Chris Worth; Jacqueline Nicholson; Catherine Fullwood; Catherine Fullwood; Indraneel Banerjee; Indraneel Banerjee (Frontiers in Endocrinology, 2023)
IntroductionEasypod-connect™ for childhood growth disorders is a unique connected system that enables transmission of injection adherence information for recombinant human growth hormone (r-hGH). Although this system has the potential to facilitate greater adherence, observational studies have shown declining adherence over prolonged periods when used without additional support. Supplemental nurse practitioner support has been envisaged but not investigated; in this study, we have undertaken feasibility analysis of nurse-led virtual reviews (NVR) in combination with easypod-connect™ in a single centre using quantitative and qualitative analyses.AimsWe aimed to test feasibility by assessing compliance with NVR, height standard deviation score (SDS) gain, adherence improvement and patient opinions.MethodsPatients using easypod™ r-hGH were recruited prospectively to a 12-month study with two telephone NVR appointments in addition to standard of care in-person hospital outpatient visits. A subset was recruited for a semi-structured interview for qualitative thematic analysis.ResultsForty-three patients of median (range) age 10.7 (6.7, 15.2) were recruited for a period of 1.1 (0.7, 1.8) years. Thirty-three (76.7%) patients were fully compliant with NVR integration with easypod-connect™, establishing feasibility. Median (inter-quartile range, IQR) height SDS improved from -1.85 (-2.44, -1.37) to -1.48 (-2.14, -1.07) (p<0.001) while adherence remained similar in the majority from study start [96.5 (88.8, 100.0)] to end [99.0 (94.0, 100.0)]. Qualitative analysis identified themes supporting patient benefit: practicalities of appointments, perceived purpose and significance of virtual reviews, and the importance of optimising growth. Four patients complained of injection pain, of whom two switched to an alternative r-hGH device.ConclusionOur study has demonstrated the feasibility of nurse-led virtual review integration with easypod-connect™ in a mixed methods study, laying the foundation for research in larger groups over longer periods. Nurse practitioner supported application of easypod-connect™ offers the potential for improved growth outcomes in all r-hGH devices providing adherence information.